Synthesis and pharmacological evaluation of [18F]PBR316: a novel PET ligand targeting the translocator protein 18 kDa (TSPO) with low binding sensitivity to human single nucleotide polymorphism rs6971. Issue 7 (19th April 2021) - Mattner, Filomena; Katsifis, Andrew; Bourdier, Thomas; Loc'h, Christian; Berghofer, Paula; Fookes, Christopher; Hung, Tzong-Tyng; Jackson, Timothy; Henderson, David; Pham, Tien; Lee, Brendan J.; Shepherd, Rachael; et al.
Abstract : PBR316 has high brain uptake, biodistribution consistent with TSPO expression and is insensitive to rs6971 polymorphism with a LAB:HAB ratio of 1.5. It can be prepared in >99% radiochemical purity, 160–400 GBq μmol −1 and >98.5% stability after 4 h. Abstract : Radiopharmaceuticals that target the translocator protein 18 kDa (TSPO) have been investigated with positron emission tomography (PET) to study neuroinflammation, neurodegeneration and cancer. We have developed the novel, achiral, 2-phenylimidazo[1, 2- a ]pyridine, PBR316 that targets the translocator protein 18 kDa (TSPO) that addresses some of the limitations inherent in current TSPO ligands; namely specificity in binding, blood brain barrier permeability, metabolism and insensitivity to TSPO binding in subjects as a result of rs6971 polymorphism. PBR316 has high nanomolar affinity (4.7–6.0 nM) for the TSPO, >5000 nM for the central benzodiazepine receptor (CBR) and low sensitivity to rs6971 polymorphism with a low affinity binders (LABs) to high affinity binders (HABs) ratio of 1.5. [ 18 F]PBR316 was prepared in 20 ± 5% radiochemical yield, >99% radiochemical purity and a molar activity of 160–400 GBq μmol −1 . Biodistribution in rats showed high uptake of [ 18 F]PBR316 in organs known to express TSPO such as heart (3.9%) and adrenal glands (7.5% ID per g) at 1 h. [ 18 F]PBR316 entered the brain and accumulated in TSPO-expressing regions with an olfactory bulb to brain ratio of 3 at 15 min and 7 at 4 h. Radioactivity was blocked by PK11195 and Ro 5-4864 but not Flumazenil. Metabolite analysis showed that radioactivity in adrenal glands and the brain was predominantly due to the intact radiotracer. PET–CT studies in mouse-bearing prostate tumour xenografts indicated biodistribution similar to rats with radioactivity in the tumour increasing with time. [ 18 F]PBR316 shows in vitro binding that is insensitive to human polymorphism and has specific and selective in vivo binding to the TSPO. [ 18 F]PBR316 is suitable for further biological and clinical studies.